The Bridge Occlusion Balloon as a safety net in a high-risk transvenous lead extraction procedure. (8th September 2017) - Pecha, Simon; Vogler, Julia; Reichenspurner, Hermann; Hakmi, Samer
Abstract: Injuries to the superior vena cava (SVC) during transvenous lead extraction (TLE) procedures are a rare but life-threatening complication. The Bridge Occlusion Balloon (BOB) is specifically designed for temporary SVC occlusion in TLE procedures. We report the first case of a 27-year-old man using the BOB as a safety net in a high-risk TLE procedure. This patient, with a congenitally corrected transposition of the great arteries and a third-degree atrioventricular block, presented with 4 dysfunctional pacemaker leads, venous stenosis and the necessity for a new pacemaker system. The leads were implanted for 10 and 19 years. The BOB was placed with a radiopaque marker at the cavoatrial junction and was inflated with 46 ml of an 80/20 saline/contrast agent mixture. An angiography was performed to confirm SVC occlusion. With the deflated balloon in place, the TLE procedure with laser and mechanical sheaths was performed. Successful extraction of 2 dysfunctional leads, as well as venous recanalization, for the new right atrial and right ventricular lead implantation was achieved. We have shown the feasibility of using powered extraction sheaths with a deflated BOB in place. This allows for immediate balloon inflation, in case of an SVC perforation.